Young Generation Taxpayer Awareness: Evidence from Balikpapan University - Yudea (Indonesian Journal of Applied Accounting and Finance, 2025)
Taxation is a crucial pillar of state finance and a civic responsibility that requires strong awareness among future taxpayers. This study aims to explore the awareness of students at Balikpapan University as potential taxpayers and to analyze the factors influencing their attitudes toward tax compliance. Using a qualitative descriptive approach through Focus Group Discussions with twelve students from both accounting and non-accounting backgrounds, the study applies thematic analysis to identify patterns of knowledge, perceptions, and attitudes toward taxation. The findings indicate that although students understand the importance of taxes for national development, their knowledge of tax regulations remains limited, particularly among non-accounting students. Sanctions are viewed as necessary but inconsistently enforced, while distrust in institutions due to corruption and weak accountability emerges as a key barrier to tax compliance. Although educational programs such as Tax Goes to Campus increase short-term awareness, they lack depth and sustainability. Students express willingness to comply voluntarily if tax systems are transparent and fair, highlighting the importance of integrating tax education into higher education and strengthening institutional credibility. These findings suggest that early and systematic tax education, supported by transparent governance, is essential to foster voluntary tax compliance among the younger generation.